Análise do desempenho térmico de habitações populares da microrregião de Guaratinguetá - SP - Mattos, Thomaz Lourenço de [UNESP] (2015)
Thermal performance is defined as the minimum expected thermal behavior of buildings in response to the external environment and conditions of use environments, seeking better indoor thermal comfort. Thermal comfort is one of the key indicators of the quality of a building and can be reached through the application of bioclimatic concepts, adapting the building to the climate and the landscape of the construction site. The adoption of bioclimatic strategies can provide high quality environmental building and energy and consequently the reduction in electricity consumption and improved health and well-being of users. In order to verify whether the indoor conditions of buildings are appropriate to the desirable or acceptable thermal comfort parameters, we use the thermal performance evaluation. As low-cost houses do not count on well-planned projects, which consider strategies for adaptation to the environment, they are objects of greater interest when checking the thermal performance. This study aims to evaluate the thermal performance of low-cost houses in the microregion of Guaratinguetá-SP, using theoretical and experimental methods, according to the performance criteria of the Brazilian standard NBR 15575/2013. Seven buildings were evaluated during summer and winter, under actual conditions of use, which showed poor performance by calculation method, being necessary to the field of measurement method, for the final evaluation of thermal performance